Analisis Kausalitas Antara Harga Saham Konvensional Dengan Harga Saham Syariah Di Indonesia (pendekatan granger causality) - Wartoyo Ayus Ahmad Yusuf (Fakultas Ekonomi dan Bisnis Islam (FEBI), Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2018)
Stock Price that occur in the share market always fluctuate over time. Stock value fluctuations will be set by the strength of supply and demand. If the supply amount is greater than the amount of demand, generally the exchange stock value will decrease, and vice versa. Not only that, competition between companies in marketing their shares also affect the stock price changes. It is clear if there is a change in price increase on syariah stock price index, will affect other stock prices. The possibility may also occur otherwise, such as a decline in the price of shares listed in the syariah stock price index so in order to compete with healthy other companies will also lower the price on the issued shares. Therefore, this study was conducted with the aim to know whether there is a reciprocal relationship between the conventional stock price with the stock price of syariah. This study uses quantitative research method by using granger causality approach. The data used are secondary data sourced from publication data of Indonesia Stock Exchange with time series based on monthly statistic report, and other sources related to the research problem. The study model used is granger causality test. After the data used tested normality, stationarity, cointegration and has known the optimum lag value then do the granger causality test using the help of software EVIEWS 8. The results of this study indicate that the conventional stock price variables listed in the LQ45 index based on statistical analysis do not significantly affect the Syariah Stock Price listed in the Jakarta Islamic Index (JII) with the ratio F value of F statistic < F table, that is 1,01 < 2,59, with a significant value of 0,3677 > 0,05. On the contrary, Syariah Stock Price Variables registered in Jakarta Islamic Index (JII) based on statistical analysis have significant effect on Conventional Stock Price which is included in index LQ45 with F value of statistic > F table, that is 3,64 > 2,59, with value significant 0,0309 < 0,05. Therefore, the result of granger causality test that no granger causality occurs between JII and LQ45. This means that JII has a relationship with LQ45, but JII and LQ45 have no two-way relationship (causality). Keywords: Stock Price, Jakarta Islamic Index (JII), LQ45, Granger Causality Test.